Current landscape and future prospects of interleukin-2 receptor (IL-2R) agonists in cancer immunotherapy - Kengo Tanigawa; William L. Redmond (OncoImmunology)
Immune checkpoint blockade (ICB) has significantly improved the survival for many patients with advanced malignancy. However, fewer than 50% of patients benefit from ICB, highlighting the need for more effective immunotherapy options. High-dose interleukin-2 (HD IL-2) immunotherapy, which is approved for patients with metastatic melanoma and renal cell carcinoma, stimulates CD8+ T cells and NK cells and can generate durable responses in a subset of patients. Moreover, HD IL-2 may have potential efficacy in patients whose disease has progressed following ICB and plays a vital role in expanding tumor-infiltrating lymphocyte (TIL) in TIL therapy. Despite its potential, the use of HD IL-2 is limited by severe toxicities such as hypotension and vascular leak syndrome. Additionally, only a few patients achieve a good outcome after HD IL-2 therapy. To address these challenges, numerous next-generation IL-2 receptor (IL-2 R) agonists have been developed to exhibit treatment effects while minimizing adverse events. This review will explore IL-2 biology, the clinical application of HD IL-2 therapy, and the development of novel IL-2 R agonists for cancer immunotherapy.